Bridging the Gap Between Product Design and Customer Engagement: Role of Self-Determined Needs Satisfaction - Hammad Bin Azam Hashmi; Chengli Shu; Syed Waqar Haider; Adeel Khalid; Yasin Munir (SAGE Open, 2021)
This study aims at exploring the influence of product design on customer engagement through self-determined needs satisfaction. This study used the survey method in three ways: (1) mall intercept approach, (2) email survey, and (3) survey through Wechat. The sample was collected from 500 customers of electronic products living in Xi’an, China. The data analysis is done through structural equation modeling. Findings show that perceived product design in terms of functional, esthetic, and symbolic design is positively related to self-determined needs (autonomy, relatedness, competence) satisfaction. Furthermore, results reveal that self-determined needs satisfaction has a positive influence on customer engagement. The moderation results show that prevention focused customers moderate the relationship between functional design and self-determined needs satisfaction. Whereas, promotion focused customers moderate the relationship between esthetic design and self-determined needs satisfaction. This study adds value to the self-determination theory by examining the link between product design dimensions and customer engagement through self-determined needs satisfaction. Furthermore, this study adds value to the existing literature on regulatory focus theory.